Methodology for the incorporation of geographic information in Wikidata - Obregón-Sierra, Ángel; López-Otero, Javier; Gavira-Narváez, Antonio; Vega-Pozuelo, Rafael F. (Revista de Estudios Andaluces, 2023)
Wikidata is a free knowledge base, editable by any user, which has experienced exponential growth since its creation to become one of the largest public knowledge repositories on the Internet at this moment. However, there are few studies on geographic information storage and analysis in Wikidata, among other reasons, because there is no explicit methodology for it. Thus, this research proposes a method that includes 6 phases that allows the introduction of a huge amount of geographic data in Wikidata, which in turn will be available for spatial analysis using a GIS. This methodology has been implemented through the introduction of a large database of geodesic 11.143 triangulation stations of Spain. It represents a contribution to geography, since it allows the use of large Wikidata databases in a GIS, which can help improve the efficiency of models that make use of such information.